Pengaruh Stres Kerja Terhadap Kinerja Karyawan: Studi Literatur - Qonita Sholihah; Khairul Ikhwan (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This study aims to identify whether work stress affects employee performance. The sample of this research is articles published in 18 accredited national journals within a period of 6 years, namely from 2017 to 2022. The sample is obtained from as many as 20 articles that discuss work stress. The research method used is charting the field method by classifying articles based on topics, methods, and research sectors. The result is that the most studied topic from the dependent variable is employee performance, and the most studied independent variable is work stress. The research sector that is mostly carried out as the object of research is the private sector. The most widely used research method is the quantitative method